Experimental evaluation of normal and shear delamination in cellulose-based materials using a cohesive zone model. (1st October 2022) - Biel, Anders; Tryding, Johan; Ristinmaa, Matti; Johansson-Näslund, Markus; Tuvesson, Oscar; Stigh, Ulf
Abstract: An experimental study to characterize properties controlling delamination of paperboard is presented. The normal and shear traction–separation laws are measured and evaluated using a double cantilever beam (DCB) and a split double cantilever beam (SCB) specimen. The DCB-experiments provides normal separation data in good agreement with results using alternative experimental techniques. From the measured data, both normal and shear fracture resistance data are obtained. A length parameter is introduced. The length parameter allows for the cohesive law to be obtained from a dimensionless master curve which is valid both for normal and shear loading. Taking advantage of the master curve, a mixed-mode potential is proposed. The mixed-mode potential is implemented as a user interface to a finite element code. As a final test, the experimental setups of the DCB and SCB specimens are simulated to validate the identified normal and shear properties.